EVALUATION OF GENETIC VARIABILITY FOR DIFFERENT FIBER AND YIELD RELATED COMPONENTS IN COTTON (GOSSYPIUM HIRSUTUM L.) - IQBAL, Z; ULLAH, MI; CHOHAN, SM; IQBAL, J; FAROOQ, MS; SARWAR, MKS; KHAN, RAR; LATIF, A; NAZAR, MZK; SALEEM, M; MAJEED, T; Ahmad, MI; et al. (Biological and Clinical Sciences Research Journal, 2023)
Cotton (Gossypium hirsutum.) is a vital commodity, and fiber and cash crop grown as an important part of cropping systems around the globe. However, Pakistan's production has not been according to its potential for many years. Its production and yield have decreased in Pakistan due to the loss of genetic diversity and lack of empirical research. Therefore, the current research was performed to evaluate the genetic diversity for sixteen yield components among 19 local and one exotic cotton (Gossypium hirsutum L.) genotypes. The experiment was conducted at the experimental site of the Department of Plant Breeding and Genetics, University of Agriculture, Faisalabad. The experiment was performed under the Randomized complete block design (RCBD) with two replications. Analysis of variance revealed significant differences among all traits for available genotypes. The mean value for seed cotton yield ranged from 106.8 to 35.5 g. Genotype ZB-18026 displayed the maximum mean value, whereas genotype ZB-18032 showed the minimum mean value for this particular trait. High heritability coupled with high genetic advance was calculated for most traits. Lint mass per seed showed the highest heritability value (99.99%). Lint mass per boll showed the lowest value of heritability coupled with genetic advance. The phenotypic coefficient of variance (PCV) was higher than most traits' corresponding genotypic coefficient of variance (GCV). Boll weight manifested the highest PCV (68.7088%) and GCV (61.0473%). While traits, such as seed index and fiber strength, showed low values of GCV and PCV. The information related to the genetic variability of genotypes for various traits can be utilized as a basis for further genetic evaluations for future breeding programs.